Bioconversion of agricultural wastes using parental, hybrid and reconstituted strains of pleurotus and lentinula - Valenzuela-Cobos, J. D.; Vásquez-Véliz, G. K.; Zied, D. C. [UNESP]; Franco-Hernández, O. M.; Sánchez-Hernández, A.; Garín-Aguilar, M. E.; Leal-Lara, H.; Valencia Del Toro, G. (Universidad Autonoma Metropolitana, 2019)
The production of parental, hybrid and reconstituted strains of Pleurotus and Lentinula was evaluated using two agricultural wastes such as wheat straw (WS) and a mixture of oak sawdust, wheat straw, millet seed, cotton seed hull and CaCO3 (AP). The productivity, morphology parameters and chemical composition of the mushrooms, and also the chemical composition of the substrates before and after harvest were determined. The parental strain Pleurotus djamor (PD) produced on WS showed the highest productivity: biological effiuciency (141.86%), production rate (2.27%) and yield (47.88%). The hybrid strain Pleurotus djamorxLentinula edodes (PD4 xLC3) cultivated on AP presented the highest productivity parameters: biological efficiency (120.01%), productivity rate (2.70%) and yield (41.10%). All the strains presented fruit bodies with pileus diameter corresponding to 5 - 9.9cm and length of stipe < 5 cm. The parental strain of Pleurotus ostreatus PO and the hybrids PO5xLC2 and PD4xLC3 cultivated on WS presented fruit bodies with highest protein content between 27.16 to 27.76% respectively, and the reconstituted strain of Pleurotus djamor PD1xPD4 produced on AP presented a protein content of 33.90%. The substrate WS used in the fructification of the parental strain of Pleurotus djamor (PD) exhibited the highest biodegradation value of lignin (28.50%), while the substrate AP used in the production of the reconstituted strain PO1xPO2 presented the highest biodegradation value of lignin (39.50%).
Bioconversión de residuos agrícolas usando cepas parentales, híbridas y reconstituidas de pleurotus y lentinula
Keywords: Agricultural Wastes; Chemical Composition; Morphology; Productivity